Seismic control performance for Pounding Tuned Massed Damper based on viscoelastic pounding force analytical method. (22nd December 2017) - Xue, Qichao; Zhang, Jingcai; He, Jian; Zhang, Chunwei; Zou, Guangping
Abstract: This paper focuses on vibration control performance of Pounding Tuned Massed Damper (PTMD) with viscoelastic pounding layers, which can dissipate energy during collision process. By using of viscoelastic pounding force analytical method, two types of pounding force models for different contact geometries are developed to illustrate interactions among pounding components in PTMD. A shake table test based on a simplified experimental structure is conducted to verify the effectiveness of single PTMD as well as the viscoelastic pounding force model. Furthermore, a parametric study for a 14-storeys steel structure is presented to investigate the performance of PTMD device in multiple degree of freedom (MDOF) system. Results from numerical simulations demonstrated that properties of viscoelastic material and gaps between mass block and the limiters in PTMD are key factors for vibration control performance. By inputting a series of seismic excitations into MDOF system, comparisons between PTMD and traditional TMD reveals that the optimized PTMD has better performance than the traditional TMD in vibration suppression in certain cases.